Ultrahigh-voltage power cable insulating material and preparation method thereof
By using low-density polyethylene, functionalized graphene and inorganic nanoparticles and other materials, the problem of poor insulation and aging resistance of traditional cable materials is solved, excellent mechanical and insulation performance is achieved, and the service life of the cable is extended.
Patent Information
- Application Number
- CN202411995928.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The insulation and aging resistance of traditional cable materials are poor, which affects the service life of the cable.
Ultra-high voltage power cable insulation materials are prepared through specific mixing and processing steps using low-density polyethylene, functionalized graphene, inorganic nanoparticles and compatibility agents.
It improves the mechanical properties and insulation properties of the insulating materials, and maintains excellent insulation properties after thermal aging test, extending the service life of the cable.
Smart Images

Figure BDA0005224524030000101 
Figure BDA0005224524030000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable insulation materials, and in particular to an ultra-high voltage power cable insulation material and a preparation method thereof. Background Art
[0002] Wires and cables are basic products used to transmit electrical (magnetic) energy, transfer information, realize electromagnetic energy conversion and constitute automated control lines. Wires and cables play a key role as a medium in power transmission and are widely used in the fields of electricity, construction, communications, automobiles, and aviation. They provide electrical equipment with power transmission, information transmission and other purposes. They are essential carriers for the development of an electrified, information-based, and intelligent society, and play an important role in promoting the development of the national economy. Cables are usually composed of conductors, insulation layers, sheaths, shielding layers, etc., among which insulation and sheaths are generally made of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), ethylene-vinyl acetate copolymer (EVA) and other materials. The performance of the insulation layer determines the service life of the cable.
[0003] Patent document CN106700195B discloses a high-voltage DC cable insulation material and a preparation method thereof. The insulation material described in the invention includes the following components in parts by weight: 100 parts of polyethylene resin; 0.1-6 parts of dopamine-modified nanoparticles; 2 parts of diisopropylbenzene peroxide; 0.1-0.5 parts of antioxidant; the dopamine is modified dopamine; and the nanoparticles are inorganic nanoparticles. The invention uses dopamine with a long chain structure to graft and modify the nanoparticles. The dopamine with a long chain structure can not only improve the dispersibility of the nanoparticles, but also significantly inhibit the injection of space charges, greatly improve the dielectric strength of the cable insulation material, and is suitable for high-voltage DC cable insulation.
[0004] However, in actual application environments, cable materials will age due to various factors, thus affecting the overall service life of the cable. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an ultra-high voltage power cable insulation material and a preparation method thereof, so as to solve the problem that traditional cable materials have poor insulation and aging resistance.
[0006] Based on the above purpose, the present invention provides an ultra-high voltage power cable insulation material, comprising the following raw materials in parts by weight: 90-100 parts of low-density polyethylene, 1-3 parts of functionalized graphene, 1.5-4.5 parts of inorganic nanoparticles, 0.1-1.5 parts of a compatibilizer, 0.1-1 parts by weight of an antioxidant, and 1-5 parts by weight of a cross-linking agent;
[0007] The preparation steps of the functionalized graphene are as follows:
[0008] S1: dispersing methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate in methanol, then dropping it into an ethylenediamine solution, stirring it at 20-25° C. under a nitrogen atmosphere for 90-100 hours, and then purifying it under reduced pressure and heating to obtain a modified substance;
[0009] S2: dispersing graphene oxide in N,N-dimethylformamide, uniformly dispersing by ultrasonication, to obtain a graphene oxide solution, then dissolving the modified substance in N,N-dimethylformamide, dissolving N,N'-dicyclohexylcarbodiimide in N,N-dimethylformamide, dissolving 4-dimethylaminopyridine in N,N-dimethylformamide, adding them together to the graphene oxide solution, reacting at 20-25°C in a nitrogen atmosphere for 90-100 hours, filtering, washing, purifying, filtering, and drying to obtain modified graphene oxide;
[0010] S3: The modified graphene oxide was dispersed in 200-300 mL of 10 mM Tris-HCl aqueous solution, and ultrasonically treated in an ice bath for 1 h, and then DA-HCl was added, stirred for 15-20 min, and reacted at 60-65 ° C for 20-24 h in a nitrogen atmosphere, and then KH570 was added, and reacted at 60-65 ° C for 8-10 h, filtered, washed, and dried to obtain functionalized graphene;
[0011] Preferably, the usage ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, methanol and ethylenediamine in step S1 is 20-30 g: 300-500 mL: 200-300 mL.
[0012] Preferably, in step S2, the amount ratio of the graphene oxide dispersion, N,N-dimethylformamide, the modifying substance, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 2-3 g: 400-650 mL: 20-25 g: 10-12 g: 6-8 g.
[0013] Preferably, the usage ratio of the modified graphene oxide, DA-HCl, KH570 and Tris-HCl aqueous solution in step S3 is 1-3 g: 5-10 g: 0.5-1: 200-300 mL.
[0014] Preferably, the density of the low-density polyethylene is 0.910-0.925 g / cm 3 , melt index is 2.1-2.2g / 10min, melting point is 112℃.
[0015] Preferably, the inorganic nanoparticles are a mixture of nano-SiO2, nano-Mg(OH)2, and nano-Al(OH)3 in a weight ratio of 1:1:1.
[0016] Preferably, the particle size of nano-SiO2 is 30-60nm.
[0017] Preferably, the particle size of nano Mg(OH)2 and nano Al(OH)3 is 50-100 nm.
[0018] Preferably, the compatibilizer is one of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene.
[0019] Preferably, the antioxidant is one of antioxidant 1010, antioxidant 300 and antioxidant BBM.
[0020] Preferably, the cross-linking agent is one of di-tert-butyl peroxide and dicumyl peroxide.
[0021] Preferably, the particle size of the graphene oxide in step S2 is 10-50 nm.
[0022] Furthermore, the present invention also provides a method for preparing an ultra-high voltage power cable insulation material, comprising the following steps:
[0023] (1) low-density polyethylene, functionalized graphene, a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2 (1:1:1), and a compatibilizer are placed in an internal mixer and kneaded for 20-25 minutes at a mixing temperature of 130-150° C. to obtain a mixed material;
[0024] (2) adding a crosslinking agent and an antioxidant to the mixed material in sequence, and kneading the mixture in an internal mixer for 10-20 minutes at a mixing temperature of 130-150° C. to obtain a mixed material;
[0025] (3) The mixture is melt-extruded and granulated at a temperature of 250-280° C. to obtain an ultra-high voltage power cable insulation material.
[0026] Beneficial effects of the present invention: The ultra-high voltage power cable insulation material of the present invention has excellent mechanical properties and insulation properties, and after a heat aging test at 90° C., it can still maintain relatively excellent insulation properties.
[0027] The ultra-high voltage power cable insulation material of the present invention is added with functionalized graphene, which ensures the excellent mechanical properties and insulation properties of the insulation material while also making it have excellent anti-aging properties. DETAILED DESCRIPTION
[0028] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0029] Example 1: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0030] (1) 20 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 300 mL of methanol under magnetic stirring, and then added dropwise to a cooled (0° C.) 200 mL of ethylenediamine solution, and stirred at 20° C. under a nitrogen atmosphere for 90 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0031] (2) 2 g of graphene oxide was dispersed in 200 mL of N,N-dimethylformamide and uniformly dispersed by ultrasonication to obtain a graphene oxide solution. Subsequently, 20 g of the modified substance was dissolved in 100 mL of N,N-dimethylformamide, 10 g of N,N'-dicyclohexylcarbodiimide was dissolved in 50 mL of N,N-dimethylformamide and 6 g of 4-dimethylaminopyridine was dissolved in 50 mL of N,N-dimethylformamide, and added to the graphene oxide solution together. The mixture was reacted at 20-25° C. and nitrogen atmosphere for 90 h. The mixture was filtered using a 0.2 μm membrane, and then washed twice with ethanol and twice with ether. The mixture was dialyzed in acetone for 48 h, filtered, and dried under vacuum freeze drying for 24 h to obtain modified graphene oxide.
[0032] (3) 1 g of modified graphene oxide was dispersed in 200 mL of 10 mM Tris-HCl aqueous solution (pH = 8.5), ultrasonically treated in an ice bath for 1 h, then 5 g of DA-HCl was added, stirred for 15 min, reacted at 60 ° C for 20 h in a nitrogen atmosphere, then 0.5 g of KH570 was added, reacted at 60 ° C for 8 h, filtered using a 0.2 μm membrane filter, then washed with deionized water 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0033] (4) 90 g of low-density polyethylene, 1 g of functionalized graphene, 1.5 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 0.1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 20 min at a mixing temperature of 130° C. to obtain a mixed material;
[0034] (5) 1 g of di-tert-butyl peroxide and 0.1 g of antioxidant 1010 were added to the mixture in sequence, and the mixture was kneaded in an internal mixer for 10 min at a mixing temperature of 130° C. to obtain a mixture;
[0035] (6) The kneaded product is melt-extruded and granulated at a temperature of 250° C. to obtain an ultra-high voltage power cable insulation material.
[0036] Example 2: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0037] (1) 25 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 400 mL of methanol under magnetic stirring, and then added dropwise to a cooled (0° C.) 25 mL of ethylenediamine solution, and stirred at 23° C. under a nitrogen atmosphere for 95 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0038] (2) 2.5 g of graphene oxide was dispersed in 250 mL of N,N-dimethylformamide and uniformly dispersed by ultrasonication to obtain a graphene oxide solution. Subsequently, 23 g of the modified substance was dissolved in 130 mL of N,N-dimethylformamide, 11 g of N,N'-dicyclohexylcarbodiimide was dissolved in 80 mL of N,N-dimethylformamide and 7 g of 4-dimethylaminopyridine was dissolved in 80 mL of N,N-dimethylformamide, and added to the graphene oxide solution together. The mixture was reacted at 23° C. and nitrogen atmosphere for 95 h. The mixture was filtered using a 0.2 μm membrane, and then washed twice with ethanol and twice with ether. The mixture was dialyzed in acetone for 48 h, filtered, and dried under vacuum freeze drying for 24 h to obtain modified graphene oxide.
[0039] (3) 2 g of modified graphene oxide was dispersed in 25 mL of 10 mM Tris-HCl aqueous solution (pH = 8.5), ultrasonically treated in an ice bath for 1 h, then 8 g of DA-HCl was added, stirred for 18 min, reacted at 63 ° C for 22 h in a nitrogen atmosphere, then 0.8 g of KH570 was added, reacted at 63 ° C for 9 h, filtered using a 0.2 μm membrane filter, then washed with deionized water 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0040] (4) 95 g of low-density polyethylene, 2 g of functionalized graphene, 3 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 23 min at a mixing temperature of 140° C. to obtain a mixed material;
[0041] (5) 3 g of di-tert-butyl peroxide and 0.5 g of antioxidant 1010 were added to the mixture in sequence, and the mixture was kneaded in an internal mixer for 15 min at a mixing temperature of 140° C. to obtain a mixture;
[0042] (6) The kneaded product is melt-extruded and granulated at a temperature of 270° C. to obtain an ultra-high voltage power cable insulation material.
[0043] Embodiment 3: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0044] (1) 30 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 500 mL of methanol under magnetic stirring, and then added dropwise to 300 mL of a cooled (0° C.) ethylenediamine solution, and stirred at 25° C. under a nitrogen atmosphere for 100 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0045] (2) 3 g of graphene oxide was dispersed in 300 mL of N,N-dimethylformamide and uniformly dispersed by ultrasonication to obtain a graphene oxide solution. Subsequently, 25 g of the modified substance was dissolved in 150 mL of N,N-dimethylformamide, 12 g of N,N'-dicyclohexylcarbodiimide was dissolved in 100 mL of N,N-dimethylformamide and 8 g of 4-dimethylaminopyridine was dissolved in 100 mL of N,N-dimethylformamide, and added to the graphene oxide solution. The mixture was reacted at 5°C and nitrogen atmosphere for 100 h. The mixture was filtered using a 0.2 μm membrane, and then washed twice with ethanol and twice with ether. The mixture was dialyzed in acetone for 48 h, filtered, and dried under vacuum freeze drying for 24 h to obtain modified graphene oxide.
[0046] (3) 3 g of modified graphene oxide was dispersed in 300 mL of 10 mM Tris-HCl aqueous solution (pH = 8.5), ultrasonically treated in an ice bath for 1 h, then 10 g of DA-HCl was added, stirred for 20 min, reacted at 65 ° C for 24 h in a nitrogen atmosphere, then 1 g of KH570 was added, reacted at 65 ° C for 10 h, filtered using a 0.2 μm membrane filter, then washed with deionized water 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0047] (4) 100 g of low-density polyethylene, 3 g of functionalized graphene, 4.5 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1.5 g of maleic anhydride grafted polyethylene were put into an internal mixer and kneaded for 5 min at a mixing temperature of 50° C. to obtain a mixed material;
[0048] (5) 5 g of di-tert-butyl peroxide and 1 g of antioxidant 1010 were added to the mixture in sequence, and the mixture was kneaded in an internal mixer for 20 min at a mixing temperature of 150° C. to obtain a mixture;
[0049] (6) The kneaded product is melt-extruded and granulated at a temperature of 280° C. to obtain an ultra-high voltage power cable insulation material.
[0050] Comparative Example 1: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0051] (1) 25 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 400 mL of methanol under magnetic stirring, and then added dropwise to a cooled (0° C.) 25 mL of ethylenediamine solution, and stirred at 23° C. under a nitrogen atmosphere for 95 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0052] (2) 2.5 g of graphene oxide was dispersed in 250 mL of N,N-dimethylformamide and uniformly dispersed by ultrasonication to obtain a graphene oxide solution. Subsequently, 23 g of the modified substance was dissolved in 130 mL of N,N-dimethylformamide, 11 g of N,N'-dicyclohexylcarbodiimide was dissolved in 80 mL of N,N-dimethylformamide and 7 g of 4-dimethylaminopyridine was dissolved in 80 mL of N,N-dimethylformamide, and added to the graphene oxide solution together. The mixture was reacted at 23° C. and nitrogen atmosphere for 95 h. The mixture was filtered using a 0.2 μm membrane, and then washed twice with ethanol and twice with ether. The mixture was dialyzed in acetone for 48 h, filtered, and dried under vacuum freeze drying for 24 h to obtain modified graphene oxide.
[0053] (3) 2 g of modified graphene oxide was dispersed in 25 mL of 10 mM Tris-HCl aqueous solution (pH = 8.5), ultrasonically treated in an ice bath for 1 h, then 8 g of DA-HCl was added, stirred for 18 min, reacted at 63 ° C in a nitrogen atmosphere for 22 h, filtered using a 0.2 μm membrane filter, then washed with deionized water 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0054] (4) 95 g of low-density polyethylene, 2 g of functionalized graphene, 3 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 23 min at a mixing temperature of 140° C. to obtain a mixed material;
[0055] (5) 3 g of di-tert-butyl peroxide and 0.5 g of antioxidant 1010 were added to the mixture in sequence, and the mixture was kneaded in an internal mixer for 15 min at a mixing temperature of 140° C. to obtain a mixture;
[0056] (6) The kneaded product is melt-extruded and granulated at a temperature of 270° C. to obtain an ultra-high voltage power cable insulation material.
[0057] Comparative Example 2: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0058] (1) 25 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 400 mL of methanol under magnetic stirring, and then added dropwise to a cooled (0° C.) 25 mL of ethylenediamine solution, and stirred at 23° C. under a nitrogen atmosphere for 95 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0059] (2) 2.5 g of graphene oxide was dispersed in 250 mL of N,N-dimethylformamide and uniformly dispersed by ultrasonication to obtain a graphene oxide solution. Subsequently, 23 g of the modified substance was dissolved in 130 mL of N,N-dimethylformamide, 11 g of N,N'-dicyclohexylcarbodiimide was dissolved in 80 mL of N,N-dimethylformamide and 7 g of 4-dimethylaminopyridine was dissolved in 80 mL of N,N-dimethylformamide, and added to the graphene oxide solution together. The mixture was reacted at 23° C. and nitrogen atmosphere for 95 h. The mixture was filtered using a 0.2 μm membrane, and then washed twice with ethanol and twice with ether. The mixture was dialyzed in acetone for 48 h, filtered, and dried under vacuum freeze drying for 24 h to obtain modified graphene oxide.
[0060] (3) 2 g of modified graphene oxide was dispersed in anhydrous ethanol, 0.8 g of KH570 was added, and the mixture was reacted at 63 ° C for 9 h, filtered using a 0.2 μm membrane filter, and then washed with deionized water for 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0061] (4) 95 g of low-density polyethylene, 2 g of functionalized graphene, 3 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 23 min at a mixing temperature of 140° C. to obtain a mixed material;
[0062] (5) 3 g of di-tert-butyl peroxide and 0.5 g of antioxidant 1010 were added to the mixture in sequence, and the mixture was kneaded in an internal mixer for 15 min at a mixing temperature of 140° C. to obtain a mixture;
[0063] (6) The mixed material is melt-extruded and granulated at a temperature of 270° C. to obtain an ultra-high voltage power cable insulation material
[0064] Comparative Example 3: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0065] (1) 25 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was dispersed in 400 mL of methanol under magnetic stirring, and then added dropwise to a cooled (0° C.) 25 mL of ethylenediamine solution, and stirred at 23° C. under a nitrogen atmosphere for 95 h, and then the methanol was removed under reduced pressure at 40° C., and then the product was heated to 60° C. to remove excess ethylenediamine, thereby obtaining a modified substance;
[0066] (2) 95 g of low-density polyethylene, 1.81 g of graphene oxide, 0.19 g of modified substance, 3 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 23 min at a mixing temperature of 140° C. to obtain a mixed material;
[0067] (3) adding 3 g of di-tert-butyl peroxide and 0.5 g of antioxidant 1010 to the mixture in sequence, and kneading the mixture in an internal mixer for 15 min at a mixing temperature of 140° C. to obtain a mixture;
[0068] (4) The mixture is melt-extruded and granulated at a temperature of 270° C. to obtain an ultra-high voltage power cable insulation material.
[0069] Comparative Example 4: An ultra-high voltage power cable insulation material, the specific preparation steps are as follows:
[0070] (1) 2 g of graphene oxide was dispersed in 25 mL of 10 mM Tris-HCl aqueous solution (pH = 8.5), ultrasonically treated in an ice bath for 1 h, then 8 g of DA-HCl was added, stirred for 18 min, reacted at 63 ° C for 22 h in a nitrogen atmosphere, then 0.8 g of KH570 was added, reacted at 63 ° C for 9 h, filtered using a 0.2 μm membrane filter, then washed with deionized water 3 times, and freeze-dried under vacuum for 24 h to obtain functionalized graphene;
[0071] (2) 95 g of low-density polyethylene, 2 g of functionalized graphene, 3 g of a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2, and 1 g of maleic anhydride grafted polyethylene were put into an internal mixer and mixed for 23 min at a mixing temperature of 140° C. to obtain a mixed material;
[0072] (3) adding 3 g of di-tert-butyl peroxide and 0.5 g of antioxidant 1010 to the mixture in sequence, and kneading the mixture in an internal mixer for 15 min at a mixing temperature of 140° C. to obtain a mixture;
[0073] (4) The mixture is melt-extruded and granulated at a temperature of 270° C. to obtain an ultra-high voltage power cable insulation material.
[0074] Performance Testing
[0075] The obtained sample was placed in a mold and pressed into a thin sheet using a flat vulcanizer. The temperature of the flat vulcanizer was controlled at 120°C, the time was 15 minutes, the pressure was 12MPa, the film length was 5cm, the width was 3cm, and the thickness was 3mm. The prepared sample was placed in a vacuum drying oven for degassing treatment, the temperature was controlled at 80°C, the time was 12h, and then the experiment was carried out;
[0076] Accelerated heat aging test: According to GB / T 11017-2002, the heat aging temperature is 90°C. The treated samples are placed in a heat aging box and the temperature is controlled at 90°C for long-term heat aging test.
[0077] Table 1 Performance test results
[0078]
[0079]
[0080] Data analysis: The ultra-high voltage power cable insulation material of the present invention has excellent mechanical properties and insulation properties, and after a heat aging test at 90°C, it can still maintain relatively excellent insulation properties.
[0081] It can be seen from Example 2 and Comparative Example 1 that the present invention grafts functionalized graphene into the cross-linked network of polyethylene, so that the mechanical properties and insulation properties of the insulating material are improved. This is mainly because, on the one hand, the grafting into the cross-linked network makes its distribution more uniform, further blocking the transmission of current. On the other hand, since dopamine exists in the cross-linked network, the compatibility between the polyethylene substrate and the inorganic nanoparticles is better.
[0082] It can be seen from Example 2 and Comparative Examples 2, 3 and 4 that the present invention improves the mechanical properties and insulating properties of the insulating material by loading the modified substance on the surface of graphene oxide and then coating it with dopamine. This is mainly because, on the one hand, the modified substance can be used as an active antioxidant to improve the anti-aging properties of the insulating material, and loading it on graphene oxide increases the loading amount of the modified substance. On the other hand, dopamine has good compatibility and can make the modified substance disperse more evenly. At the same time, its coating can shield the high conductivity of graphene oxide, ultimately achieving the goal of ensuring that the insulating material has excellent mechanical properties and insulating properties while also having excellent anti-aging properties.
[0083] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. An ultra-high voltage power cable insulation material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of low-density polyethylene, 1-3 parts of functionalized graphene, 1.5-4.5 parts of inorganic nanoparticles, 0.1-1.5 parts of a compatibilizer, 0.1-1 parts by weight of an antioxidant, and 1-5 parts by weight of a crosslinking agent; The preparation steps of the functionalized graphene are as follows: S1: dispersing methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate in methanol, then adding dropwise to an ethylenediamine solution, stirring at 20-25° C. under a nitrogen atmosphere for 90-100 hours, then purifying under reduced pressure and heating to obtain a modified substance; S2: dispersing graphene oxide in N,N-dimethylformamide, uniformly dispersing by ultrasonication, to obtain a graphene oxide solution, then dissolving the modified substance in N,N-dimethylformamide, dissolving N,N'-dicyclohexylcarbodiimide in N,N-dimethylformamide, dissolving 4-dimethylaminopyridine in N,N-dimethylformamide, adding them together to the graphene oxide solution, reacting at 20-25°C in a nitrogen atmosphere for 90-100 hours, filtering, washing, purifying, filtering, and drying to obtain modified graphene oxide; S3: Disperse the modified graphene oxide in 200-300 mL of 10 mM Tris-HCl aqueous solution, ultrasonically treat in an ice bath for 1 h, then add DA-HCl, stir for 15-20 min, react at 60-65 ° C in a nitrogen atmosphere for 20-24 h, then add KH570, react at 60-65 ° C for 8-10 h, filter, wash and dry to obtain functionalized graphene; The usage ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, methanol and ethylenediamine in step S1 is 20-30 g: 300-500 mL: 200-300 mL; The amount ratio of graphene oxide, N,N-dimethylformamide, modifying substance, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step S2 is 2-3 g: 400-650 mL: 20-25 g: 10-12 g: 6-8 g; The usage ratio of the modified graphene oxide, DA-HCl, KH570 and Tris-HCl aqueous solution in step S3 is 1-3 g: 5-10 g: 0.5-1: 200-300 mL.
2. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The density of the low-density polyethylene is 0.910-0.925 g / cm 3 , melt index is 2.1-2.2g / 10min, melting point is 112℃.
3. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The inorganic nanoparticles are a mixture of nano-SiO2, nano-Mg(OH)2 and nano-Al(OH)3 in a weight ratio of 1:1:
1.
4. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The compatibilizer is one of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene.
5. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 300 and antioxidant BBM.
6. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The cross-linking agent is one of di-tert-butyl peroxide and diisopropylbenzene peroxide.
7. The ultra-high voltage power cable insulation material according to claim 1, characterized in that: The particle size of the graphene oxide in step S2 is 10-50 nm.
8. A method for preparing an ultra-high voltage power cable insulation material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) low-density polyethylene, functionalized graphene, a mixture of nano-Mg(OH)2, nano-Al(OH)3 and nano-SiO2 (1:1:1), and a compatibilizer are placed in an internal mixer and kneaded for 20-25 minutes at a mixing temperature of 130-150° C. to obtain a mixed material; (2) adding a crosslinking agent and an antioxidant to the mixed material in sequence, and kneading the mixture in an internal mixer for 10-20 minutes at a mixing temperature of 130-150° C. to obtain a mixed material; (3) The mixture is melt-extruded and granulated at a temperature of 250-280° C. to obtain an ultra-high voltage power cable insulation material.
Citation Information
Patent Citations
Insulation materials for high voltage DC cables and their preparation methods
CN106700195B